Pneumonectomy in rats delays gastric emptying rate: Effect of mediastinal shift - (:unkn) unknown (My University, 2003)
Objective: To elucidate possible alterations in the gastric emptying rate after pneumonectomy, we designed an experimental study in rats and looked for the mechanical and neural factors. Methods: Following the intubations, a left thoracotomy was performed and the left lung was removed (pneumonectomy; n=48) or not removed (sham-operated; n=8). Control rats had no throacotomy (n=14). Gastric functions (gastric emptying rates of solid and liquid meals) were evaluated 1 week after the surgical procedure. In some rats with pneumonectomy, to test the involvement of thoracic vagal afferents in the gastric functions, capsaicin was applied perivagally, while in some rats hemithorax was filled with bone wax to prevent pneumonectomy-induced mediastinal shift. Results: Gastric emptying rates of solid and liquid meals in the sham-operated and control groups were not different from each other. In the pneumonectomy group, gastric emptying rates of solid and liquid meals were significantly delayed compared to sham group (respectively; p<0.001 and p<0.05). Afferent denervation by capsaicin did not change gastric emptying rates compared with vehicle-treated animals. Intrathoracic application of bone wax abolished the delay in gastric emptying rates of both solid and liquid meals induced by pneumonectomy (p<0.01). Conclusion: The present results suggest that pneumonectomy in rats delays gastric emptying rate and denervation of the capsaicin-dependent vagal afferent fibers has no effect, while filling the cavity of the removed lung with bone wax abolishes the pneumonectomy-induced delay in both liquid and solid emptying rates.
Keywords: Capsaicin; Gastric emptying; Pneumonectomy